What drives the creation of nested markets? A qualitative case study of food markets in West Bengal, India - Abe Chatterjee, Shantonu; Bernzen, Amelie (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
The ethics of ecological production, egalitarianism, and democratic control underpinning recent research directions in agri-environmental governance are common to many of the issues explored in the alternative economies literature. One way in which these ethics are put into practice in agri-environmental governance is through the concept of ‘nested markets’. Using qualitative methods of interviews and a focus group discussion, we examine newly constructed markets for food at different spatial scales in West Bengal, India. We find that multifunctional farmers and other actors along the supply chain started to construct and/or strengthen their own outlets and channels to reach consumers and to sell their products. Some of these markets build on long, historically deeply-rooted experiences, such as local periodic markets; others are relatively new constructions, making use of internet marketing platforms or messaging services and direct home delivery. Although they are market segments that are nested in the wider commodity markets for food, they have a different nature, different dynamics, a different redistribution of value added, and different relations between producers and consumers. Surprisingly, environmental issues were considered to be less important motivations than the creation of solidarity between producers and consumers. A deeper examination of these markets suggests new possible answers to the question of how to improve the sustainability of agricultural systems within an alternative economies framework.